การใช้ภูมิปัญญาท้องถิ่นสําหรับการดูแลสุขภาพตนเองท่ามกลางผู้สูงวัยในตำบลหนึ่งของจังหวัดพะเยา - พรหมมา เนตรนภา; สมจิตร พรพนา (Health Science, Science and Technology Reviews, 2015)
วัตถุประสงค์ของการศึกษาคือกำหนดหาภูมิปัญญาท้องถิ่นของการดูแลตนเองของผู้สูงวัยในตำบลหนึ่งของจังหวัดพะเยา ดำเนินการด้วยแบบสอบถามเชิงโครงสร้างระหว่างชาวบ้านผู้สูงวัย 84 คน เช่นเดียวกับสัมภาษณ์เชิงลึกหมอสมุนไพร 12 คนผู้มีประสบการณ์เยียวยาแขนงนี้เฉลี่ยนาน 32 ปี การรักษาโรคด้วยสมุนไพรใช้ในภาวะหลากหลายเป็นต้นว่า ภูมิแพ้ หอบหืด หวัด เจ็บคอ และป้องกันยุงกัด พิสัยหลากหลายของการปลูกสมุนไพรในชุมชน ยกตัวอย่าง บอระเพ็ด ไพล ฟ้าทะลายโจร ว่านหางจระเข้ และตะไคร้หอม ข้อได้เปรียบของการเยียวยาด้วยสมุนไพร ประกอบด้วย เป็นผลภัณฑ์ธรรมชาติอย่างแท้จริง ราคาถูกกว่า หาง่าย และผลข้างเคียงด้านลบน้อยกว่า ขณะที่ข้อเสียเปรียบประกอบด้วยใช้เวลานานกว่าต่อการแสดงผลดี มีส่วนผสมอันอาจเกิดผลข้างเคียง และไม่เหมาะสมในการรักษาภาวะทางการแพทย์บางอย่าง The use of local wisdom for health care among aging in a subdistrict, Phayao province Natnapa Promma* , Pornpana Somjit Division of Community Health, Department of Public Health, School of Medicine, University of Phayao, Phayao Province 56000 The purpose of the study is to determine the local wisdom of the aging self-care at a subdistrict, Phayao Province. The structural questionnaire was conducted among 84 aging villagers, as well as in-depth interview of 12 traditional herbal healers who had the average of 32-year experience in this healing field. The herbal medicine was used to treat many conditions such as allergy, asthma, common cold, cough, sore throat, and mosquito bite prevention. A wide variety of herbs were grown in the community for example Tinospora cordifolia, Zingiber purpureum Roscoe, Andrographis paniculata, aloe vera, and citronella grass. The advantages of herbal remedy were completely natural product, less expensive, available, and fewer negative side effects while the disadvantage included longer time period for improved results to show, containing ingredients that may cause side effect, and inappropriate in treating certain medical condition.